Latvijas Universitātes vēstures liecības atmiņas institūciju krājumos: referātu tēžu krājums - Latvijas Universitāte. 81. starptautiskā zinātniskā konference (LU Akadēmiskais apgāds, 2023)
Latvijas Universitātes 81. starptautiskās zinātniskās konferences ietvaros Latvijas Universitātes Muzeja organizētās konferences “Latvijas Universitātes vēstures liecības atmiņas institūciju krājumos” referātu tēžu krājums.

Collection of the abstracts of the conference organized by the Museum of the University of Latvia “Historical Evidence of the University of Latvia in the Collections of Memory Institutions” as part of the 81th International Scientific Conference of the University of Latvia.
Historical Evidence of the University of Latvia in the Collections of Memory Institution : Abstracts
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects; atmiņu institūcijas; LU karoga vēsture; Latvijas armijas virsnieku sagatavošana; Latvijas Universitātes vēsture; LU Muzeja kolekcijas